Evaluasi Program Boarding School dengan model CSE-UCLA - Sofiah Sofiah (AL-BURHAN, 2023)
The aim of this study was to evaluate the overall implementation program of Boarding School Darul Adzkiya’ at MAN 2 Kudus. This evaluation research used evaluation model of CSE-UCLA (Center for the Study of Evaluation – University of California in Los Angeles) which consists of five components namely system assessment, program planning, program implementation, program improvement, and program certification. This study used Mix Method (qualitative and quantitative). The technique of collecting data used questionnaire, interview, observation, and documentation. As for the data analysis used descriptive analysis method. The location of the study was conducted at Islamic State Boarding School (MAN) 2 of Kudus. The research results showed that: System assessment for the need level and also the long-term goals of the establishment of boarding school Darul Adzkiya' which was to be achieved had been appropriate with the purpose of establishment; Program Planning, for job programs, educator profiles, students profiles, class administration and also learning infrastructure were technically good.; Implementation program on the results of the study it could be said that it was good; Program Improvement from all sides, could be said that it had functioned well.; Program certification for learning outcomes aspects was still lack because it was only based on the value of public speaking. By the improvements in those parts that were lack, the Darul Adzkiya boarding school will be more perfect in the future and produce the best quality.